Poate funcţiona economia socială pentru toţi? - Duminică, Gelu; Mocanu, Cristina (Calitatea Vieții, 2017)
Branded as a solution to the most and diverse problems caused by the progressive withdrawal of state from the social protection provision, the scientific literature rarely analysed the prerequisites that could support the development of a robust and sustainable social economy sector, and with focus on its success within the disadvantaged communities. Traditionally the majority of a specific community, most possibly the “white” majority (Sevulpeda, Syrett, Calvo, 2010) represented also the majority of the social economy sector developed within that community. Thus the conditions that could support a functional social economy for marginalized ethnic communities were rarely questioned. The first part of the article analyses the literature from an historical perspective in order to retain those prerequisites that lead to the emergence and success of social economy mostly in the capitalist states. The second part tackles some problems of marginalized communities, some of them being also ethnic communities, and discusses when and how the “social economy” panacea could be transferred in communities living in poverty, exclusion, marginalization and lack of solidarity.